(untitled) - Shiels, Frederick L. (Lexington, Mass., 1980)
Tokyo and Washington: Dilemmas of a mature alliancewas conceived in fits and starts from three very different sources. Although in the late 1960s and 1970s abundant hardbacks and paperbacks on Japan and Japanese-American relations were appearing-including several by authors with wider backgrounds and readership than Japanese matters alone-there was a decided gap between such works and the relating of country studies and alliance studies to more general literature on foreign policy making and political science.
Keywords: Japan,United states,World politics; Foreign relations,Foreign relations; 1945-; United states,Japan